Implementation of scheduling in hybrid power domain non‐orthogonal multiple access system considering adaptive modulation and coding schemes selection - Kryukov, Yakov V.; Pokamestov, Dmitriy A.; Rogozhnikov, Eugeniy V. (International journal of communication systems, 2024)
Summary Communication systems that simultaneously combine orthogonal (OMA) and nonorthogonal multiple access (NOMA) are currently under research. Such systems are called hybrid and have more flexibility in user multiplexing, which allows for increased system capacity. One of the main focus areas of research in such systems is radio resource scheduling. The existing research works on scheduling approaches are based on the Shannon's formula, which can be used to obtain the limit capacity by ideal modulation and coding schemes (MCS). However, it is more correct to consider scheduling based on the real capacity. To get it, one should consider the performance of real MCSs with finite code length; however, they are very rarely taken into account in NOMA research. The reason is that one of the basic unresolved problems in NOMA is MCS selection for users. To solve it, we have presented a table of joint pairwise MCS combinations with their adaptive selection for NOMA. In this work, we propose a radio resource scheduling approach for the OMA/NOMA system based on real MCSs that uses our own method of joint MCS selection for two NOMA users. By performing the simulation of the proposed scheduling approach, we have obtained both total and user capacity in the OMA/NOMA system, as well as the distribution of traffic among users, demonstrating the execution of the scheduling strategies. The research is focused on radio resource scheduling in an OMA/NOMA hybrid multiple access communication system considering the performance of modulation and coding schemes taken from the LTE specification. We have proposed the implementation of main scheduling strategies in the hybrid system and obtained their performance by simulation. Also, user traffic of a conventional OMA system and the hybrid OMA/NOMA system are compared.